The Impact of Game-based Learning on Sustainability Education for Next Generations: a Case Study Analysis - Wójcik, Joanna; Świętoniowska, Joanna; Jakieła, Jacek (International Journal of Research in E-learning, 2025)
Higher education institutions face increasing pressure to equip students with the competencies needed to address complex sustainability challenges. Game-based learning (GBL) offers a promising approach to engaging students and fostering the development of knowledge, skills, and attitudes required for sustainable development. This study examines the potential of the SEED simulation game, designed using the Octalysis Framework, to improve sustainability education. A mixed-methods study was conducted with 45 university students who participated in the SEED game and completed a post-game evaluation questionnaire. Quantitative analyses included descriptive statistics, correlations, and principal component analysis of motivational factors. Qualitative feedback was also analysed thematically. The results indicate that the SEED game fostered moderate to high levels of student engagement, motivation, and perceived sustainability knowledge gains. Development & Accomplishment and Social Influence & Relatedness emerged as the most effective motivational drivers. A strong positive correlation was found between engagement and motivation. Students particularly valued the game’s realism, personalization, and opportunities for social interaction. The findings underscore the value of integrating well-designed simulation games into sustainability education, especially for new generations who have specific learning preferences. They also highlight key considerations for future game design and educational practice, including the importance of transparent feedback mechanisms and addressing diverse learner expectations. This study contributes to ongoing efforts to leverage gamification to support transformative learning for sustainable development, highlighting benefits for students in terms of engagement and motivation, and for teachers who gain an innovative tool to explain complex sustainability issues. These findings are in line with similar experiences reported at European universities.